Zoster Eye Disease Study: Rationale and Design. Issue 5 (28th May 2022) - Cohen, Elisabeth J.; Hochman, Judith S.; Troxel, Andrea B.; Colby, Kathryn A.; Jeng, Bennie H.
Abstract : Purpose: The purpose of this study was to describe the rationale and design of the Zoster Eye Disease Study (ZEDS). Methods: ZEDS is a National Eye Institute–supported randomized clinical trial designed to determine whether 1 year of suppressive valacyclovir in patients with herpes zoster ophthalmicus (HZO) reduces complications because there is currently no high-quality evidence to support its use. Eligible patients are 18 years and older, immunocompetent, have a history of a typical rash at disease onset, and have had a record of active epithelial or stromal keratitis or iritis within 1 year before enrollment. Exclusion criteria include estimated glomerular filtration rate less than 45 or pregnancy. The primary endpoint is the time to first occurrence of new or worsening dendriform epithelial keratitis, stromal keratitis without or with ulceration, endothelial keratitis, or iritis due to HZO during 12 months of study treatment requiring prespecified treatment changes. The study has 80% power to detect a 30% difference between treatment groups, with a 30% rate of endpoints by 1 year assumed among controls. Secondary and exploratory questions include whether there is a persistent treatment benefit during the 6 months after treatment, whether development of postherpetic neuralgia varies by treatment group, and whether vaccinations against herpes zoster affect study outcomes and coronavirus disease 19 status. Results: Over approximately 4 years, over 400 study participants have been enrolled. Conclusions: ZEDS aims to provide scientific evidence on whether suppressive valacyclovir treatment improves outcomes in HZO and should become the standard of care.